Cryptogenic chronic hepatitis: looking for an ideal diagnostic algorithm - Cançado, Guilherme Grossi Lopes; Candolo, Aline Coelho Rocha; Nardelli, Mateus Jorge; Zitelli, Patricia Momoyo; Mazo, Daniel Ferraz de Campos; Oliveira, Claudia Pinto; Cunha-Silva, Marlone; Greca, Raquel Dias; Araújo, Roberta Chaves; Alustau, Amanda Sacha Paulino Tolentino; Couto, Cláudia Alves; Roque, Gabriel Rezende de Lima; et al. (Frontiers in Gastroenterology, 2023)
Introduction Cryptogenic chronic hepatitis is a growing cause of liver transplants, affecting 5%–15% of patients with chronic liver diseases. This study aimed to identify underlying causes of cryptogenic liver disease in a Brazilian cohort and propose a new diagnostic algorithm, including investigation for metabolic-dysfunction-associated fatty liver disease (MAFLD) and lysosomal acid lipase deficiency (LAL-D). Methods A retrospective analysis was conducted on 326 patients with presumed cryptogenic hepatitis. Results Using Czaja’s algorithm, non-alcoholic fatty liver disease was diagnosed in 21.3% of patients, while alpha-1 antitrypsin deficiency, alcoholic liver disease, autoimmune hepatitis, hemochromatosis, biliary-related hepatitis, viral hepatitis, Budd–Chiari syndrome, glycogenosis, drug-induced liver injury, and Wilson’s disease were diagnosed in smaller proportions (< 3.5% each). LAL-D was found in 1% of patients, and 53.6% of patients remained with cryptogenic hepatitis. The etiology of the liver disease in a subset of patients undergoing liver transplantation was updated post hoc based on explant histology, and non-alcoholic steatohepatitis was found in 52.5% of patients. By incorporating the concept of MAFLD, the new algorithm could diagnose 49.1% of patients, reducing the number of individuals without an etiological diagnosis by 11.4%. Conclusion One-third of patients with initially presumed cryptogenic liver disease were diagnosed with MAFLD. LAL-D should be considered in patients with chronic liver disease of unknown etiology. The updated diagnostic algorithm proposed in this study could improve diagnostic accuracy and aid in the management of patients with cryptogenic hepatitis.